Comparison Between Conventional and Electrocautery Approach in The Treatment of Pericoronitis - Feby Monika; Sri Pramestri Lastianny; Vincensia Maria Karina (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Pericoronitis refers to an intraoral inflammation caused by an infection affecting the gum tissue surrounding a tooth that is either erupting or partially erupted. The gum tissue is known as operculum which entrapped food debris and hard to clean, causing inflammation. It frequently occurred in lower third molars although it can be happened with any erupting teeth. This case report was to discuss the comparison result of removing operculum between using conventional technique with scalpel and electrocautery. Case: A 22-year-old female patient visiting RSGM Prof Soedomo, Yogyakarta with a chief complaint of pain in the lower left and right back tooth for the past five months, interfering with her meals and causing discomfort. Extraoral examination showed no abnormalities and intraoral examination showed operculum covering the distal occlusal of tooth 38 and 48. Case Treatment: Operculectomy was performed at region 38 using scalpel and blade while at region 48 using electrocautery to eliminate pericoronitis. Discussion: The bleeding while excision in operculectomy with scalpel and blade was quite excessive and need an effort to control. In the other hand, bleeding was mild in operculectomy with electrocautery. There was no swelling in electrocautery surgery while mild swelling was found in conventional approach Conclusion: Therefore, the treatment results demonstrate that both technique showing good healing and removing any discomfort but electrocautery approach was painless compared with scalpel and blade approach. Operators should have to know the associated risk and management of post operative complications.